Diversity and uniqueness of Family business in the North of Portugal (European Journal of Interdisciplinary Studies, 2023)
Family businesses are the most omnipresent form of business organisations at the international and national levels. In Portugal, family firms account for more than 70 percent of all businesses, contributing with 50 percent in employment creation. Yet, most of the existing literature does not converge in a consensual and operative definition of what are core elements which distinguish family business from non-family business. Therefore, it is crucial to extend our knowledge on important family business topics due to the broadness, diversity, uniqueness and growth potential of family business in the whole world. In this sense, the ongoing project “Roadmap for Portuguese Family Businesses” (NORTE2020/FEDER) is focused on providing a better understanding and assessment of the impact of family businesses in the North of Portugal on the local, national and international economies. This research addresses a major problem that has been identified in Europe and consists in the lack of institutional visibility, particularly of accurate and up-to-date statistics in this sector. This paper begins by identifying some of the interesting research questions that emerge from examining the business family portraits. Then, based on some preliminary empirical findings gathered from ongoing research, first of all, we intend to identify interesting profiles of family business by mobilising some socioeconomic variables; and secondly, to point out major challenges faced by Portuguese family business.